Study of the impact of irradiation and temperature on physical and chemical characteristics of paracetamol - Al-Maydama, Hussein Manaa Ali; Abduljabbar, Adlia Ahmad Mohammad (Eclética Química, 2024)
Pure paracetamol samples were subjected to temperature (40 °C) and light (sunlight, UV-lamp, and γ-ray) for time intervals. Treatment impact on the extent of chemical and physical impairments in the treated samples was pursued by comparing the results obtained from thermogravimetric analysis and differential scanning calorimeter (TGA/DSC), scanning electron microscopy (SEM), X-ray diffraction (XRD), high-performance liquid chromatography (HPLC), and photocatalytic decomposition process. Thermal analysis behavior, lifetime prediction, thermal stability, kinetics (i.e., Ea, Z, n), and thermodynamic (∆G*, ∆H*, and ∆S*) parameters were investigated for samples before and after exposure to heat and light from curves of the non-isothermal gravimetric analysis (TGA) at a heating rate of 10 °C min–1 and with an association of Coats-Redfern and the other standard equations. Changes in crystallinity percentage were calculated relative to the untreated sample using measurements of DSC and XRD. In some treated samples, changes in morphology and purity were observed in SEM images and HPLC results. Kinetic parameters were determined, and the photocatalytic degradation percentage was discussed.